2015
DOI: 10.1101/gad.267286.115
|View full text |Cite
|
Sign up to set email alerts
|

ALS mutations in TLS/FUS disrupt target gene expression

Abstract: Amyotrophic lateral sclerosis (ALS) is caused by mutations in a number of genes, including the gene encoding the RNA/DNA-binding protein translocated in liposarcoma or fused in sarcoma (TLS/FUS or FUS). Previously, we identified a number of FUS target genes, among them MECP2. To investigate how ALS mutations in FUS might impact target gene expression, we examined the effects of several FUS derivatives harboring ALS mutations, such as R521C (FUS C ), on MECP2 expression in transfected human U87 cells. Strikingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 82 publications
5
42
0
Order By: Relevance
“…Consistent with our data, recent evidence showed that FUS-R521C can form stable FUS- Bdnf mRNA or FUS- MECP2 mRNA complexes, which impair transcription and/or RNA splicing suggesting that FUS mutants could disrupt target gene expression at a post-transcriptional level4960. Recent RNA-seq transcriptome analyses have identified more target genes that are differentially regulated in FUS-WT and ALS-linked FUS mutants in cellular and animal models49.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our data, recent evidence showed that FUS-R521C can form stable FUS- Bdnf mRNA or FUS- MECP2 mRNA complexes, which impair transcription and/or RNA splicing suggesting that FUS mutants could disrupt target gene expression at a post-transcriptional level4960. Recent RNA-seq transcriptome analyses have identified more target genes that are differentially regulated in FUS-WT and ALS-linked FUS mutants in cellular and animal models49.…”
Section: Discussionsupporting
confidence: 91%
“…The mRNA was found to be present with mutant FUS in cytoplasmic aggregates by both biochemical analysis and FISH, suggesting that the transcript is sequestered. These results suggest that mutant FUS aggregation can affect the stability and translation of mRNA targets through direct sequestration of RNAs as well as pre-mRNA splicing through sequestration of splicing factors (Coady and Manley 2015).…”
Section: Fusmentioning
confidence: 95%
“…DNA FUS-responsive elements were later found enriched within promoter regions of genes shown to respond transcriptionally to FUS levels (Tan et al 2012). One such gene, MECP2, biologically interesting due to its relationship to the neuroregressive disease Rett syndrome, was found to be misspliced in cells transfected with mutant, but not wild-type, FUS (Coady and Manley 2015). Interestingly, the splice isoform of MECP2 promoted by mutant FUS was found to have increased RNA stability yet express lower protein levels.…”
Section: Fusmentioning
confidence: 99%
“…Dysregulation of RNA and protein expression in neurons has deleterious consequences and contributes to numerous neurological and psychiatric diseases (Darnell, 2013; Pilaz and Silver, 2015). For example, expression of variants of the TLS/ FUS RNA binding protein found in amyotrophic lateral sclerosis patients causes aberrant gene expression in human cells, including of MECP2 (Coady and Manley, 2015). Similarly, copy-number variations in the NUDT21 gene found in patients with neurological disease increase the fraction of MECP2 mRNA molecules with long 3′ UTRs (Gennarino et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, copy-number variations in the NUDT21 gene found in patients with neurological disease increase the fraction of MECP2 mRNA molecules with long 3′ UTRs (Gennarino et al, 2015). Total MECP2 mRNA levels are elevated in patient-derived cells (Gennarino et al, 2015) or human cells expressing TLS/FUS variants (Coady and Manley, 2015), but MeCP2 protein levels are decreased in both cases. Thus, measuring translation changes in the manner described here that can detect and quantify alternative transcripts and 3′ UTRs is essential when studying diseases involving genetic alterations to post-transcriptional control factors.…”
Section: Discussionmentioning
confidence: 99%